Protection of Inheritance Rights for Balinese Men Who Convert to Another Religion - Sadewa, M.Ilham Akbar; Anugrah, Afrian; Lestari, Ahdiana Yuni (Jurnal Penegakan Hukum dan Keadilan, 2025)
This study discussed how legal protection guarantees the inheritance rights of Balinese men who convert. The research method used a normative legal approach by utilizing primary, secondary, and tertiary legal materials. The research materials were analyzed prescriptively. The study shows that according to Balinese custom, a man will be recognized as an heir and has the right to receive inheritance if he has the same religion as the testator, such as Hinduism. Legally, a child who apostatizes from his religion, in this case, leaving the Balinese or Hindu religion, remains an heir. Article 830 of the Civil Code states that inheritance occurs due to death, and Article 838 of the Civil Code emphasizes that heirs are those who have legitimate blood relations. In essence, according to the Civil Code, inheritance can be given to heirs even though they have a different religion from the testator or even though the heir no longer follows customary law or his religion. Thus, the state provides a guarantee that Balinese men who have a different religion from the testator will still receive protection to receive a share of the inheritance according to the Civil Code.